Vinyl - Bartmanski, Dominik, 1978- author.
1 online resource
Keywords: Recent years have seen not just a revival, but a rebirth of the analogue record. More than merely a nostalgic craze, vinyl has become a cultural icon. As music consumption migrated to digital and online, this seemingly obsolete medium became the fastest-growing format in music sales. Whilst vinyl never ceased to be the favorite amongst many music lovers and DJs, from the late 1980s the recording industry regarded it as an outdated relic, consigned to dusty domestic corners and obscure record shops. So why is vinyl now experiencing a rebirth of its cool'?Dominik Bartmanski and Ian Woodward explore this question by combining a cultural sociological approach with insights from material culture studies. Presenting vinyl as a multifaceted cultural object, they investigate the reasons behind its persistence within our technologically accelerated culture. Informed by media analysis, urban ethnography and the authors' interviews with musicians, DJs, sound engineers, record store owners, collectors and cutting-edge label chiefs from a range of metropolitan centres renowned for thriving music scenes including London, New York, Tokyo, Melbourne, and especially Berlin, what emerges is a story of a modern icon.